Religious Education in the Digital Era: Facing Modern Challenges with Islamic Principles - Fatmawati, Fatmawati; Firdaus, Andrian (Jurnal Ilmiah Profesi Pendidikan, 2023)
This research aims to explore religious education in the digital era and how Islamic principles can be applied to face modern challenges. The research method used is a literature review involving in-depth analysis of relevant sources in the study of religious education and digital technology. Literature review techniques involve searching for articles, books, and online documents related to the topic. Data were analyzed qualitatively by exploring the main findings from the collected literature. The results show that the integration of digital technology in religious education can provide significant benefits in achieving Islamic educational goals. However, there are also challenges such as protecting religious and cultural values in the digital era that need to be addressed. The implications of this research are the need for the development of educational strategies that balance technology with Islamic values.